Communicating with parents in neonatal intensive care units: The impact on parental stress. Issue 4 (April 2017) - Enke, Christian; Oliva y Hausmann, Andrés; Miedaner, Felix; Roth, Bernhard; Woopen, Christiane
Highlights: We model 66 NICUs regarding specific stress in parents of VLBW infants. We examine effects of communicational and informational support on parental stress. Main predictors for stress are parents´ younger age and infant's severe prognosis. Empathy is most appropriate to reduce communication related stress in parents. Further aspects of Family-Centred Care need to be strengthened to reduce parental stress. Abstract: Objective: To analyse stress in parents whose infants with very low birth weight have just concluded high-level care in a Neonatal Intensive Care Unit (NICU). More specifically, we aimed 1) to identify groups of parents in the NICU who are particularly at risk of experiencing stress, and 2) to explore the effects of clinical staffś communication on parental stress. Methods: Our multi-center-study evaluated views from 1277 parents about care for 923 infants in 66 German NICUs. Answers were linked with separately evaluated medical outcomes of the infants. Separate generalised mixed models estimated the influence of personal, medical and communication-related characteristics on specific parental stress. Results: Parents of a younger age and those of infants with severe prognoses were more likely to experience stress. While empathetic communication as one aspect of staffś communication was shown as appropriate in reducing parental stress, an initial introduction and the quantity of information were only slightly associated with lower levels of stress. Conclusion: Results provide evidence for the need to involve parents empathetically from the beginning of their child's stay in the NICU. Practice implications: Staff in the NICU should communicate empathetically and help to reduce stress in parents particularly at risk.